#TITLE_ALTERNATIVE# - SYAH (NIM 22290001), IRDAM
Many efforts have been proposed to improve the oil recovery, especially in the enhanced oil recovery by introducing the knowledge related to reservoir characterization. This is due to nature of the reservoir which is characterized by non-uniform system. This phenomenon is strongly affected by the hydrocarbon distributions and their fluid flow properties in the reservoir. To acquire the better analysis results and in conformity with the actual reservoir conditions, the analysis method of reservoir heterogeneity have been developing quickly, especially by using reservoir simulation models. For about the last five year, the fractal-geostatistic method has been developed to characterize reservoir heterogeneities. Based on the geological processes of reservoir development, there is a spatial correlation among the heterogeneity of reservoir parameters which could be represented by semivariogram models. The publicated research showed that the result of calculation using this method fairly reflected the reservoir heterogeneity characterization and to draw near to the actual reservoir conditions. The fractal-geostatistic method which has been developing recently is the annealing simulation method. This method based on the stochastic conditional simulation method, statistical mechanics and annealing process (i.e. a process to strengthen the structure of metal or glass by heating and cooling). In this research, annealing simulation method was used to calculate the thickness and porosity distribution values for 9 layers in Tanjung Tiga Timur structure at Prabumulih field. Semivariogram models and cummulative distribution functions are calculated using thickness and porosity data of the drilled wells. Then both distribution values could be calculated by using annealing simulation method. The results also show that faults as reservoir boundaries in simulation grids can affect the calculations.